Diagnostic Accuracy and Surgical Outcomes of Deep Infiltrating Endometriosis Involving the Urinary Tract: A Systematic Review: Surgical Outcomes of Deep Infiltrating Endometriosis Involving the Urinary Tract - Khan, Muhammad Azam; Rahman, Misbah Ur; Ullah, Sami; Mehmood, Zara; Majeed, Zahid; Faisal, Sanober (Pakistan Journal of Health Sciences, 2026)
Deep infiltrating endometriosis (DIE) involving the urinary tract represents a severe phenotype of endometriosis that poses major diagnostic and surgical challenges. Accurate preoperative imaging and optimal surgical management are essential to prevent silent obstruction and long-term renal damage. Objectives: To evaluate the diagnostic accuracy of imaging modalities and to summarize surgical outcomes in patients with urinary tract deep infiltrating endometriosis. Methods: This systematic review was conducted in accordance with PRISMA 2020 guidelines. PubMed, Scopus, and the Cochrane Library were searched for studies published between January 2018 and March 2025. Diagnostic-accuracy studies and outcome-only surgical cohorts were synthesized as distinct evidence streams. Methodological quality was assessed using QUADAS-2 for diagnostic studies and the Newcastle–Ottawa Scale for surgical cohorts. Results: Twelve studies were included, comprising two formal diagnostic-accuracy studies and ten surgical outcome cohorts. Transvaginal ultrasonography using the IDEA protocol demonstrated high diagnostic performance (sensitivity 93.9%, specificity 99.4%, accuracy 98.7%), while magnetic resonance imaging showed good sensitivity (83.3%) and excellent negative predictive value (93.5%). Most surgical cohorts reported favorable postoperative outcomes with low urinary tract–specific recurrence when managed in specialized centers. However, none of the studies reported confidence intervals or complete diagnostic contingency matrices. Conclusions: Transvaginal ultrasonography and magnetic resonance imaging are complementary and highly specific modalities for diagnosing urinary tract DIE, and minimally invasive surgery yields favorable outcomes. Standardized diagnostic reporting and prospective multicenter diagnostic-accuracy studies are required to strengthen evidence-based clinical pathways.